Character Building of New Students in The School Environment Introduction Period at SMP Negeri 1 Bangli - Ekayana Putra, Dewa Ngakan Made; Setyaningsih, Setyaningsih (International Journal of Multidisciplinary Sciences, 2024)
Schools have the duty and responsibility to shape students’ character in a good direction, so activity is needed to support the national education objectives by implementing the school environment introduction period (MPLS). This activity aims to make students understand and learn more about the school environment, facilities and infrastructure, programs, and school rules. Implementing MPLS for new students at SMP Negeri 1 Bangli will provide benefits, especially for students to adapt well. This study aimed to examine the reasons for character building, patterns of character building, and the implications of character building during the school environment introduction period at SMP Negeri 1 Bangli. Based on this analysis, it was found that the school environment introduction period (MPLS) at SMP Negeri 1 Bangli aimed to introduce the school environment, facilities and infrastructure in the school, school programs, school rules, and so on, so that new students could adapt well to SMP Negeri 1 Bangli. Patterns of character building in the MPLS implementation at SMP Negeri 1 Bangli were well-arranged, starting from Pre-MPLS, MPLS period, and Post-MPLS. The implications of character building in the MPLS implementation at SMP Negeri 1 Bangli were being able to choose and determine the desired skill program according to their interests and talents, having a good knowledge of the school rules and regulations of SMP Negeri 1 Bangli, being able to know the rights and obligations that must be carried out, fostering a sense of humanity and mutual respect for fellow human beings.